N-Acetyl-D-glucosamine-coated polyamidoamine dendrimer modulates antibody formation via natural killer cell activation - Hulikova, Katarina; Benson, Veronika; Svoboda, Jan; Sima, Petr; Fiserova, Anna (International immunopharmacology, 2009)
N-Acetyl-D-glucosamine-coated polyamidoamine dendrimer (GlcNAc8) was shown previously to exhibit binding affinity to the rat recombinant NKR-P1 molecule (known in mice also as NK1.1) and to induce NK cell-mediated cytotoxicity. In this study, we investigated whether GlcNAc8 modulates antibody formation as activated NK cells were reported to participate in its regulation. C57BL/6 mice treated with GlcNAc8 and intact controls were immunized either with sheep red blood cells (SRBCs), 2,4-dinitrophenylated-lipopolysaccharide (DNP-LPS) or keyhole limpet hemocyanin (KLH) for evaluation of splenic antibody forming cell counts and serum immunoglobulin (Ig) levels. In vitro Ig formation was determined using supernatants of spleen mononuclear cells (SMCs) and CD49b or NK1.1-depleted SMC subpopulations. Serum antigen-specific IgG2a levels were also measured in DBA/2 and BALB/c mice (NK1.1-negative mouse strains on the basis of flow cytometric analysis) which possess different Nkr-p1c gene form than C57BL/6 ones. A significant increase in anti-SRBC IgG forming cells, serum levels of anti-KLH as well as anti-DNP IgG and IgG2a was observed after GlcNAc8 administration in C57BL/6 mice. IgM levels in supernatants of SMCs stimulated in vitro simultaneously with DNP-LPS and GlcNAc8 were significantly mounted compared with supernatants of SMCs primed with the antigen alone, but this enhancement was blocked after depletion of CD49b-positive or NK1.1-positive cells. In DBA/2 and BALB/c mice, GlcNAc8 influenced neither serum levels of anti-KLH nor anti-DNP IgG2a. These results indicate that GlcNAc8-induced upregulation of antibody formation is triggered by NK cell stimulation and depends on expressed NKR-P1 isoforms, particularly NKR-P1C.
Keywords: Hemocyanins; Rats; Mice, Inbred BALB C; antigeny Ly; Killer Cells, Natural; Immunoglobulins; tvorba protilátek; Antibody-Producing Cells; buňky produkující protilátky; myši inbrední C57BL; Acetylglucosamine; Immunologic Factors; Mice; NK Cell Lectin-Like Receptor Subfamily B; Dendrimers; imunologické faktory; lektinové receptory NK-buněk - podrodina B; Antibody Formation; krysa rodu Rattus; dendrimery; B-lymfocyty; Animals; hemokyanin; ženské pohlaví; Antigens, Ly; zvířata; B-Lymphocytes; NKT buňky; Mice, Inbred DBA; myši inbrední BALB C; myši; imunoglobuliny; myši inbrední DBA; buňky NK; Female; Mice, Inbred C57BL; Natural Killer T-Cells; acetylglukosamin